IMPLEMENTATION OF A MOVEMENT SYMBOL LEARNING SYSTEM FOR DEAF CHILDREN IN THE HYANG LALA NUSANTARA DANCE AT GARUDA WISNU KENCANA, BALI - I Gede Gunadi Putra (SOSIOEDUKASI, 2026)
This article examines the implementation of a sign-of-movement system as a dance learning medium for deaf children involved in the performance of Hyang Lala Nusantara Dance at Garuda Wisnu Kencana (GWK) Cultural Park, Jimbaran, Bali. Hyang Lala Nusantara Dance is a large-scale cultural tourism performance that integrates various Indonesian traditional dances and involves children with special needs, particularly deaf children, alongside non-disabled dancers within a shared performance setting. This study focuses on three main aspects: (1) the design and implementation of the sign-of-movement system in the dance learning process for deaf children; (2) the effectiveness of the system in supporting participants’ engagement during live performances; and (3) the inclusive pedagogical values embedded in the learning and performance practices. This research employs a qualitative approach using observation, in-depth interviews, and documentation studies as data collection techniques. The findings reveal that the sign-of-movement system developed by I Wayan Suatra Negara and I Ketut Alit Putra Wijaya represents an innovative pedagogical approach that bridges communication barriers in dance education. The implementation of this system has proven effective in assisting deaf children in understanding, memorizing, and performing choreographic sequences in a structured manner, thereby enabling their active participation in large-scale public performances. These findings indicate that the sign-of-movement system contributes significantly to the development of inclusive, adaptive, and empowering arts education models for learners with special needs in Indonesia.